Ethiopian universities climate teaching and research advancement process by integrating climate change into academic curricula through diverse approaches - Recha, John W.M.; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Under RUFORUM, partnering with universities in Eastern and Southern Africa to advance climate research by integrating climate change into academic curricula through diverse approaches, included comprehensive curriculum overhauls, introduction of new programs, specialized trainings, and student clubs.